Alpha-1 Antitrypsin Z Variant (AAT PI*Z) as a Risk Factor for Intrahepatic Cholestasis of Pregnancy - Kosinski, Przemyslaw; Kedzia, Malgorzata; Mostowska, Adrianna; Gutaj, Pawel; Lipa, Michal; Wender-Ozegowska, Ewa; Rozy, Adriana; Chorostowska-Wynimko, Joanna; Wielgos, Miroslaw; Jezela-Stanek, Aleksandra (Frontiers in Genetics, 2021)
Background: Intrahepatic cholestasis of pregnancy (ICP; prevalence 0.2–15.6%) is the most common pregnancy-related liver disorder. It may have serious consequences for a pregnancy, including increased risk of preterm delivery, meconium staining of amniotic fluid, fetal bradycardia, distress, and fetal demise. In cases of high bile acids (>100μmol/L), patients have 10-fold increase in the risk of stillbirth. Biophysical methods of fetal monitoring, such as cardiotocography, ultrasonography, or Doppler have been proven unreliable for risk prediction in the course of intrahepatic cholestasis. Therefore, we believe extensive research for more specific, especially early, markers should be carried out. By analogy with cholestasis in children with inherited alpha-1 antitrypsin deficiency (AATD), we hypothesized the SERPINA1 Z pathogenic variant might be related to a higher risk of cholestasis in pregnancy. This study aimed to investigate the most common AATD variants (Z and S SERPINA1 alleles) in a group of cholestatic pregnant women. Results: The Z carrier frequency was calculated to be 6.8%, which is much higher compared to the general population [2.3%; the Chi-squared test with Yates correction is 6.8774 (p=0.008)]. Conclusion: Increased prevalence of SERPINA1 PI*Z variant in a group of women with intrahepatic cholestasis may suggest a possible genetic origin of a higher risk of intrahepatic cholestasis in pregnancy.